Diagnosis and surgical treatment of liver echinococcosis - Shaprinskyi , V.O.; Vorovskyi , O.O.; Kaminskyi , O.A.; Pashynskyi , Ya.M. (Medicni Perspektivi, 2021)
The results of treatment of 72 patients with echinococcosis of the liver were analyzed, women – 62 (86.2%), men – 10 (13.8%). Primary echinococcosis was detected in 69 (95.8%) patients, secondary – in 3 (4.2%). Among instrumental research methods, ultrasound and computed tomography examination were of diagnostic value. Single liver cysts were found in 63 (87.5%) patients, multiple – in 9 (12.5%). Among patients with solitary cysts, the right lobe was more often affected than the left – 48 (66.7%) vs 24 (33.3%) cases. Echinococcosis of central localization was less common and was noted in 8 (11.1%) cases. Echinococcosis complications were observed in 16 (22.2%) patients. Among them, most often there were suppurations of the cyst – in 13 (18.1%); a bursting of the cyst into the free abdominal cavity – in 1 (1.4%), in the pleural cavity – 1 (1.4%), in the biliary tract – in 1 (1.4%). Partial or complete liming of the hand was observed in 12 (16.7%) patients. In 20 (27.8%) cases, the operation was performed from the upper median access, in 42 (58.3%) – from oblique hypochondria accesses by Kocher or by Fedorov. Pericystectomy was performed in 48 (66.7%) patients, in 8 (11.1%) patients underwent resections of liver segments with an echinococcal cyst, in 4 (5.6%) – cyst opening with removal of contents and treatment of its cavity. Laparoscopic echinococectomy was used in 12 (16.7%) patients. In the postoperative period complications were observed in 16 (22.2%) patients. The use of the welding electrocoagulator EK-300M "Swarmed" in the thermal rehabilitation of the walls of the residual cavity after echinococectomy allowed to reduce blood loss from 2200±210 ml to 250±50 ml. With the use of laparoscopic echinococectomy, intraoperative blood loss was reduced by 9 times (р=0.0001); duration of operation – 2 times (р<0.05), stay in hospital – 3.3 times (р=0.002). There were no fatal outcomes. Before and after operation antirelapse antiparasitic therapy with albendazole (Vormil) was performed in two cycles of 28 days, separated by a 14-day break. The dose at body weight over 60 kg was 400 mg 2 times a day, and for less than 60 kg the drug was calculated at a rate of 15 mg/kg/day. There were 2 (2.8%) cases of relapse, there was no mortality.